Витоки та історичний розвиток пенітенціарної ідеї в системі філософського знання - Шанідзе, Надія Олександрівна (НТУ "ХПІ", 2017)
У статті висвітлені актуальні питання щодо становлення та розвитку пенітенціарної філософії в Україні і світі. Визначається теоретичне підґрунтя та історико-філософська база розвитку пенітенціарної ідеї та її філософське значення для розвитку суспільства та особистості. Особлива увага приділяється філософським вченням про мораль, право, справедливість та злочин, як головним категоріям та поняттям, на яких повинна ґрунтуватися пенітенціарна філософія.

The article deals with current issues of formation and development of the penal philosophy in Ukraine and abroad. Determined by the theoretical foundations and historical-philosophical basis of formation of the penitentiary idea and its philosophical significance for the development of society and the individual. In the framework of the penitential idea, the analysis of the concepts of socialization and resocialization, as well as the influence of the social environment on the implementation of these processes. Particular attention is paid to philosophical teachings about morality, law, justice and crime as the main categories and concepts on which to base penitentiary philosophy. The necessity of rethinking the penitentiary philosophical idea in the conditions of the modern society's transformation.
Keywords: право; мораль; свобода; закони природні; law; morality; freedom; natural laws